REMEDIASI GAME TAMASA PADA MATERI TATA NAMA SENYAWA TERHADAP HASIL BELAJAR SISWA KELAS X - Juniardi Juniardi; Rody Putra Sartika; Lukman Had Hadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe aim of this study is to determine whether there is a significant difference before and after using the tamasa game on the learning achievements of class Xb SMA Graduation Pontianak on simple compound nomenclature material. The form of research used was Pre-experimental design with one-group pretest-posttest design. The sample selection technique was done by purposive sampling technique, with the research sample being class Xb Pontianak Graduation High School. Data collection tools used were learning achievements tests, unstructured interview guidelines, and observation sheets. The results of the description of the data from the pretest and posttest were different before and after using the tamasa game on learning achievements. In conclusion, there is a significant difference before and after using the tamasa game on the learning achievements of class Xb SMA Graduation Pontianak on simple compound nomenclature material.Keywords: Learning Outcomes, Simple Compound Names, Tamasa Games